High‐Rate, Large Capacity, and Long Life Dendrite‐Free Zn Metal Anode Enabled by Trifunctional Electrolyte Additive with a Wide Temperature Range. Issue 21 (26th May 2022) - Lin, Chuyuan; Yang, Xuhui; Xiong, Peixun; Lin, Hui; He, Lingjun; Yao, Qi; Wei, Mingdeng; Qian, Qingrong; Chen, Qinghua; Zeng, Lingxing
Abstract: Aqueous Zn‐ion batteries (AZIBs) have been recognized as promising energy storage devices due to their high theoretical energy density and cost‐effectiveness. However, side reactions and Zn dendrite generation during cycling limit their practical application. Herein, ammonium acetate (CH3 COONH4 ) is selected as a trifunctional electrolyte additive to enhance the electrochemical performance of AZIBs. Research findings show that NH4 + (oxygen ligand) and CH3 COO – (hydrogenligand) with preferential adsorption on the Zn electrode surface can not only hinder Zn anode directly contact with active H2 O, but also regulate the pH value of the electrolyte, thus suppressing the parasitic reactions. Additionally, the formed SEI is mainly consisted of Zn5 (CO3 )2 (OH)6 with a high Zn 2+ transference number, which could achieve a dendrite‐free Zn anode by homogenizing Zn deposition. Consequently, the Zn||Zn symmetric batteries with CH3 COONH4 ‐based electrolyte can operate steadily at an ultrahigh current density of 40 mA cm –2 with a cumulative capacity of 6880 mAh cm –2, especially stable cycling at −10 °C. The assembled Zn||MnO2 full cell and Zn||activated carbon capacitor also deliver prominent electrochemical reversibility. This work provides unique understanding of designing multi‐functional electrolyte additive and promotes a long lifespan at ultrahigh current density for AZIBs. Abstract : Zn metal anode enabled by CH3 COONH4 electrolyte additive for dendrite‐free embraced extraordinary rate‐performance and high reversibility with a cumulative capacity of 6880 mAh cm –2 at an ultrahigh current density of 40 mA cm –2, superior to other Zn anode. The Zn||Zn symmetrical cells with attractive cycling performance stabilize over 900 h at a low temperature of −10 °C.